Determinants of early initiation of breastfeeding in Ethiopia: a population-based study using the 2016 demographic and health survey data - James Rufus John; Sabuj Kanti Mistry; Getahun Kebede; Narendar Manohar; Amit Arora (BMC, 2019)
Abstract Background Timely breastfeeding initiation is a simple but important measure that has protective effects on infants and mothers. This study aims to determine the predictors of early breastfeeding initiation among mothers residing in Ethiopia. Methods This study employed the 2016 Ethiopian Demographic and Health Survey data. A total of 5546 children born during the last 24 months at the time of survey were included for analysis from nine regional states and two city administration areas. Socio-demographic and socio-economic factors including individual, household and community-level factors were examined of their significance against the outcome variable of early initiation of breastfeeding using a mixed-effect logistic regression model. Results The proportion of infants who had timely initiation of breastfeeding was 74.3% (n = 3064). In the multivariate logistic regression analysis, mothers who delivered with assistance of one or more health professionals had 68% (AOR 1.68; 95% CI: 1.23, 2.29) higher odds of initiating timely breastfeeding. In addition, mothers delivering by a caesarean section had 86% reduced odds of early breastfeeding initiation (AOR 0.14; 95% CI: 0.09, 0.22) when compared to mothers who had vaginal delivery. In terms of socio-demographic factors, the odds of early breastfeeding initiation were more than two and half times higher particularly for mothers residing particularly in Oromiya (AOR 2.58; 95% CI: 1.84, 3.63) and Southern Nations Nationalities and Peoples (SNNP) (AOR 2.75; 95% CI: 1.86, 4.05). In addition, timely breastfeeding initiation was also significantly associated with wealth index with wealthier mothers having 43% higher odds compared to mothers of poorest households (AOR 1.43; 95% CI: 1.07, 1.92). Other factors such as age, gender and birth order of the infant also had significant associations with early breastfeeding initiation. Conclusion Early breastfeeding initiation in Ethiopia is inextricably associated with various socio-demographic, biomedical, and socio-economic factors. The study findings can potentially inform mothers and the wider community on the benefits of timely breastfeeding initiation and policymakers and community leaders to target health promotional interventions and resources where needed.